Aqueous and Ethanol Extracts of Australian Cane Toad Skins Suppress Pro‐Inflammatory Cytokine Secretion in U937 Cells via NF‐κB Signaling Pathway. Issue 12 (15th June 2016) - Zulfiker, Abu Hasanat Md.; Hashimi, Saeed M.; Qi, Ji; Grice, I. Darren; Wei, Ming Q.
ABSTRACT: Toad skin extracts, such as aqueous extracts (AE) of Chinese toad skins, have demonstrated therapeutic benefits for a range of diseases including pain, inflammation, swelling, heart failure, and various types of cancers. In this study, we investigated the anti‐inflammatory potential of an AE (0.1–10 μg/mL) and a 60% ethanol extract (EE; 0.1–10 μg/mL) from Australian cane toad ( Bufo marinus ) skins and the known bioactive compound, bufotenine (BT; 0.1–10 nM). The assay employed a model of the human monocyte cell line U937 stimulated with lipopolysaccharide (LPS) and phorbol 12‐myristate 13‐acetate (PMA) for the release of tumor necrosis factor (TNF)‐α and interleukin (IL)‐6. We demonstrated that AE, EE, and BT significantly inhibited the release and expression of TNF‐α and IL‐6 in a dose‐dependent manner when the cells were pre‐treated at non‐cytotoxic concentrations. Further investigation revealed that the inhibition of TNF‐α and IL‐6 release and expression was associated with the suppression of nuclear factor (NF)‐kappa (κ)B activation. These results indicate that AE, EE, and BT are strong inflammation inhibitors, thus have the potential for further development as anti‐inflammatory therapeutic agents from a natural source regarded as a feral pest in Australia. J. Cell. Biochem. 117: 2769–2780, 2016. © 2016 Wiley Periodicals, Inc. Abstract : Aqueous, 60% ethanol extracts of Australian cane toad skin, and their principal constituent bufotenine inhibit the release and expression of tumor necrosis factor (TNF)‐alpha and interleukin (IL)‐6 in lipopolysaccharide (LPS) and phorbol 12‐myristate 13‐acetate (PMA)‐stimulated human monocyte cells (U937). This suppression is occurred via nuclear factor (NF)‐kappa (κ)B signaling pathway.